Testing the predictive validity of combine tests among junior elite football players: an 8-yr follow-up - Yao, P.-L.; Huard Pelletier, V.; Lemoyne, J. (The Sport Journal, 2020)
Purpose: The objective of this study was to assess the relationship and contribution of physical performance test results on the final selection of an elite under-18 football selection camp. Methods: Data were drawn from 2 876 players divided into seven position groups (DB, DL, OL, LB, QB, RB, and WR) collected over an 8-year span. Players` evaluations included performance tests (10-yd dash, 20-yd dash, 40-yd dash, 20-yd pro agility shuttle, 3-cone drill, broad jump, vertical jump, power max test) and anthropometric measures (height and weight). Student t tests were calculated for selected and non-selected groups for all positions. Results: Mean comparisons showed that for most measures, selected players obtained significantly better results than non-selected players. Linear regression models were generated for all groups, and every position was found to have its own unique prediction model. The best models were those of the DL (R2 = 0.222), OL (R2 = 0.207) and LB (R2 = 0.204), and the overall explained variance for each model was considered low (R2 = 0.173). Weight, height and 40-yd dash were the most predominant factors in all models. Conclusion: Individually, selection camp results effectively discriminate between selected and non-selected players; together, however, they explain only a limited part of the final selection for each position. Applications in sport: These results suggest that the predictive capacity of the football combine could be improved in terms of the selection of elite football players.